The association of six autoimmune bullous diseases with thyroid disorders: a population‐based study. (17th June 2022) - Kridin, K.; Hübner, F.; Linder, R.; Schmidt, E.
Abstract: Background: The association of autoimmune bullous diseases (AIBDs) with thyroid disorders remains to be profoundly investigated. Objective: To evaluate the epidemiological association between six AIBDs and thyroid disorders. Methods: A population‐based cross‐sectional study enrolled patients with bullous pemphigoid (BP), mucous membrane pemphigoid (MMP), epidermolysis bullosa acquisita (EBA), pemphigoid gestationis (PG), pemphigus vulgaris (PV) and pemphigus foliaceus (PF). Patients with these six AIBDs were compared with six age‐ and sex‐matched control groups regarding the prevalence of thyroiditis and hyperthyroidism. Logistic regression was used to calculate the odds ratio (OR) and 95% confidence interval (CI) for thyroid disorders. Results: The study population included 1, 743, 251, 106, 126, 860 and 103 patients with BP, MMP, EBA, PG, PV and PF respectively. The corresponding control groups consisted of 10, 141, 1, 386, 606, 933, 5, 142 and 588 matched controls respectively. A significant association was found between thyroiditis and BP (OR, 1.98; 95% CI, 1.18–3.35; P = 0.010), MMP (OR, 7.02; 95% CI, 1.87–26.33; P = 0.004) and PV (OR, 2.73; 95% CI, 1.45–5.15; P = 0.002). With regards to hyperthyroidism, PF was the only AIBD to demonstrate significant comorbidity (OR, 2.42; 95% CI, 1.13–5.21; P = 0.024). EBA and PG were not found to cluster with any of the investigated thyroid conditions. Conclusion: Patients with BP, MMP, PV and PF experience an elevated burden of thyroid disorders. Patients with these AIBDs presenting with suggestive symptoms may be carefully screened for comorbid thyroid disorders.